2005
DOI: 10.1007/s00415-005-0739-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in bulbar– and spinal–onset amyotrophic lateral sclerosis

Abstract: We performed a longitudinal study of frontal and temporal lobe functions in patients with amyotrophic lateral sclerosis (ALS) and compared the evolution of cognitive performance with that of motor deficits in patients with spinal and bulbar-onset of the disease. Fifty two patients suffering from sporadic ALS according to the El Escorial criteria were examined; 37 patients had a spinal, 15 a bulbar onset of the disease. The data profile included examinations at entry (E1), every four months at follow-up (E2, E3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 44 publications
(58 reference statements)
8
101
2
1
Order By: Relevance
“…There have been attempts to determine whether clinical features are correlated with the presence of cognitive and behavioral testing. Some studies have found cognitive impairment to be more common in people with bulbar onset than limb onset of ALS [32]. However, other studies suggest that site of onset has no influence on the presence of cognitive impairment [33][34][35].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There have been attempts to determine whether clinical features are correlated with the presence of cognitive and behavioral testing. Some studies have found cognitive impairment to be more common in people with bulbar onset than limb onset of ALS [32]. However, other studies suggest that site of onset has no influence on the presence of cognitive impairment [33][34][35].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There is increasing evidence that not only do 2-5% of ALS patients present an ALS/dementia complex but also that patients with classical ALS without obvious clinical evidence of cognitive deficits may have subtle changes in frontal cortical function (Ludolph et al, 1992;Kew et al, 1993b;Lulé et al, 2005;Lomen-Hoerth et al, 2002). The cognitive impairment has been reported as more pronounced in ALS patients with a bulbar onset compared to patients with spinal onset (Abrahams et al, 1997;Strong et al, 1999;Lomen-Hoerth et al, 2002;Schreiber et al, 2005) and is also evident in patients with primary lateral sclerosis (PLS; Piquard et al, 2006). Longitudinal investigation of ALS patients (up to 18 months) revealed that cognitive dysfunction in ALS occurred early in the disease course and that the cognitive deficits may not progress in synchrony with motor decline, but distinctly more slowly (Schreiber et al, 2005).…”
Section: Functional Imaging Of Extramotor Paradigms In Mndmentioning
confidence: 99%
“…The cognitive impairment has been reported as more pronounced in ALS patients with a bulbar onset compared to patients with spinal onset (Abrahams et al, 1997;Strong et al, 1999;Lomen-Hoerth et al, 2002;Schreiber et al, 2005) and is also evident in patients with primary lateral sclerosis (PLS; Piquard et al, 2006). Longitudinal investigation of ALS patients (up to 18 months) revealed that cognitive dysfunction in ALS occurred early in the disease course and that the cognitive deficits may not progress in synchrony with motor decline, but distinctly more slowly (Schreiber et al, 2005). Functional imaging studies confirm hypoperfusion in the resting state in the frontal cortex in ALS with or without cognitive deficits (Ludolph et al, 1992;Anzai et al, 1990;Tanaka et al, 1993).…”
Section: Functional Imaging Of Extramotor Paradigms In Mndmentioning
confidence: 99%
“…32,33 Cognitive impairment has been reported as more pronounced in ALS patients with a bulbar onset compared with patients with spinal onset. [34][35][36][37] Longitudinal investigation of ALS patients revealed that cognitive dysfunction in ALS occurred early in the disease course and that the cognitive deficits may not progress in synchrony with motor decline, but may occur distinctly more slowly. 37 Functional neuroimaging has supported the clinical findings of frontal cortical involvement not only in patients with an ALS/dementia complex but also in patients with ALS and subclinical cognitive impairment: hypoperfusion in the frontal cortex in ALS with or without cognitive deficits measured with PET 32 and fMRI 38 and association of reduced frontal executive function and reduced activity in fronto-parietal areas measured with PET.…”
Section: Functional Imaging Of Extramotor Paradigms In Motor Neuron Dmentioning
confidence: 99%